1985
DOI: 10.1021/bi00329a004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soybean lipoxygenase 1 by N-alkylhydroxylamines

Abstract: Micromolar concentrations of N-octylhydroxylamine dramatically increase the induction period in the conversion of linoleic acid to 13(S)-hydroperoxy-cis-9,trans-11-octadecadienoic acid (13-HPOD) catalyzed by soybean lipoxygenase 1. The induction period produced by N-octylhydroxylamine is abolished by 13-HPOD but not by the corresponding hydroxy acid. Addition of a catalytic amount of lipoxygenase to a mixture of 13-HPOD and N-octylhydroxylamine results in consumption of approximately 1 mumol of 13-HPOD/mumol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 26 publications
(35 reference statements)
6
49
0
2
Order By: Relevance
“…Hence, the search for new cholinesterase inhibitors is considered to be an important and ongoing strategy to introduce new drug candidates for the treatment of Alzheimer's disease and other related diseases 25 . Lipoxygenases catalyze the addition of molecular oxygen to fatty acids containing a cis-1, 4-pentadiene system to give unsaturated fatty acid hydro peroxide 26,27 . It has been found that these LOX products play a key role in variety of disorders such as bronchial asthma, inflammation 28 and tumor angiogenesis 29 .…”
Section: Enzyme Inhibitory Potentialmentioning
confidence: 99%
“…Hence, the search for new cholinesterase inhibitors is considered to be an important and ongoing strategy to introduce new drug candidates for the treatment of Alzheimer's disease and other related diseases 25 . Lipoxygenases catalyze the addition of molecular oxygen to fatty acids containing a cis-1, 4-pentadiene system to give unsaturated fatty acid hydro peroxide 26,27 . It has been found that these LOX products play a key role in variety of disorders such as bronchial asthma, inflammation 28 and tumor angiogenesis 29 .…”
Section: Enzyme Inhibitory Potentialmentioning
confidence: 99%
“…Often the most effective treatments are ligands which inhibit the breakdown of acetylcholine. Lipoxygenases catalyze the addition of molecular oxygen to fatty acids containing a cis-1, 4-pentadiene system to give unsaturated fatty acid hydro peroxide (Clapp et al, 1985). It has been found that these lipoxygenase products play a key role in variety of disorders such as bronchial asthma, inflammation and tumor angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Lipoxygenase activity was assayed using the methods as described previously [17,18], with slight modifications. A total volume of 200 μL assay mixture contained 150 μL sodium phosphate buffer (100 mM, pH 8.0), 10 μL test compound and 15 μL purified lipoxygenase (Sigma, USA).…”
Section: Lipoxygenase Assaymentioning
confidence: 99%